Enhancing MSME Capacity Through the Utilization of QRIS as a Digital Payment System in Dukuh Setro Subdistrict, Surabaya: Peningkatan Kapasitas UMKM Melalui Pemanfaatan QRIS sebagai Sistem Pembayaran Digital di Kelurahan Dukuh Setro Surabaya - Fajria Ulumin Nafiah; Aulya Dista Yasah; Nasywa Athaya Muthmainnah Rahman; Agnes Tresia Silalahi (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The digital transformation in payment systems presents both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs). Although QRIS has been introduced as a practical and efficient cashless payment solution, some MSMEs still lack optimal understanding of its utilization. This community service activity aimed to improve the digital literacy of MSMEs in Dukuh Setro Subdistrict, Surabaya, through socialization and technical assistance in using QRIS. The implementation method included planning, information dissemination, socialization with Bank Mandiri, and technical assistance for QRIS registration and activation. A participatory approach was adopted to ensure the activities aligned with the actual needs of business actors. The results showed an increase in participants’ understanding of QRIS benefits and its operational mechanism, with most participants successfully activating their accounts and expressing readiness to implement QRIS in their daily business activities. This activity not only supports MSME digitalization but also strengthens financial literacy and prepares business actors to adapt to technological developments in the digital era.